A retrospective study of the effect of testicular biopsy extracted spermatozoa in intracytoplasmic sperm injection (ICSI) on reproductive outcomes in assisted reproductive treatment (ART) - Oosthuizen, Micke (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.